Mortality patterns due to dementia among older adults aged 60 to 69 years in Brazil (Research, Society and Development, 2025)
Population aging has intensified the burden of dementia on health systems, particularly in middle-income countries such as Brazil. This study aimed to describe mortality patterns due to dementia among individuals aged 60 to 69 years in Brazil between 2000 and 2023. An ecological time-series study was conducted using secondary data from the Mortality Information System (SIM/DATASUS). Deaths with Alzheimer’s disease (G30), vascular dementia (F01), or unspecified dementia (F03) as the underlying cause, according to ICD-10, were included. A total of 15,943 deaths were recorded during the study period, with Alzheimer’s disease accounting for 83.3% of cases. A progressive increase in dementia-related mortality was observed over time, particularly after 2010. Mortality distribution by sex was balanced, with a slight predominance among women in recent years. Most deaths occurred among white individuals, married individuals, and those with low educational attainment. The Southeast and South regions concentrated the majority of deaths, especially in the states of São Paulo, Minas Gerais, Rio de Janeiro, and Rio Grande do Sul. These findings highlight the growing relevance of dementia-related mortality in earlier stages of aging and underscore the need to strengthen epidemiological surveillance, early diagnosis, and public policies aimed at reducing inequalities associated with dementia in Brazil.